Strategi Kampanye Public Relations Pemerintah Kota Bekasi dalam Program Vaksinasi Massal Covid-19 - Troyuda, Andykha; Khoiruddin, Khoiruddin; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This research This study aims to find out how the Bekasi City Government designed and implemented a PR campaign in the covid-19 mass vaccination program using the Ostegaard campaign model. This research was carried out using a qualiative descriptive method with primary and secondary data through data collection techniques, namely in-depth interviews, observations, and documentation studies.The results of this study explained that the Public Relations Campaign regarding the Covid-19 Mass Vaccination program implemented by the Bekasi City Government was divided into several stages, first, conducting fact-finding activities which were re-divided into several methods such as through media monitoring activities to see community conditions, as well as direct socialization activities to observe public opinion.Second, carry out the stages of designing campaign activities such as designing campaign objectives, campaign messages, campaign channels, and determining campaign actors. Third, carry out campaign activities, which consist of several activities such as through the media and through face-to-face. The last is the campaign evaluation process through media monitoring and press release management.